Decentralized Clinical Trials (Dcts): Opportunities, Challenges And The Future Of Remote Research (The Review of Diabetic Studies, 2024)
Decentralized Clinical Trials (DCTs) represent a transformative shift in clinical research, leveraging digital technologies to move clinical trials from traditional, site-based models to more flexible, patient-centric approaches. This shift has been accelerated by the growing use of telemedicine, wearable devices, mobile applications, and artificial intelligence (AI). DCTs improve accessibility for participants by eliminating geographical barriers and reducing the logistical burden of trial participation. Moreover, they provide more diverse and representative patient populations, leading to more generalizable and inclusive clinical data. The integration of AI enhances the efficiency of DCTs by optimizing patient recruitment, real-time data analysis, and personalized medicine strategies, thereby improving patient outcomes. AI-driven tools can predict patient responses, identify optimal treatment strategies, and reduce dropout rates, thus accelerating trial timelines and minimizing costs. Despite these advancements, DCTs face challenges related to data privacy, regulatory compliance, and the integration of complex technologies across various platforms. Ensuring secure and reliable data handling, meeting regulatory standards across regions, and addressing technological infrastructure gaps are critical obstacles to the widespread adoption of DCTs. This paper explores the opportunities and challenges of DCTs, highlighting the potential of AI and other digital health technologies to reshape clinical trials, enhance patient engagement, and improve the efficiency of drug development. The future of clinical research will likely see further integration of AI and digital health tools, driving more efficient, cost-effective, and inclusive clinical trials.